2008
DOI: 10.3797/scipharm.0804-20
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Pharmacophore Modeling, and Biological Evaluation of Novel 5H-Thiazolo[3,2-a]pyrimidin-5-one Derivatives as 5-HT2A Receptor Antagonists

Abstract: Novel 5H-thiazolo[3,2-a]pyrimidin-5-one derivatives linked through an ethylene bridge to various phenylpiperazine groups were prepared for evaluation as 5-HT 2A receptor antagonists. The target compounds 11a-p were prepared through the initial synthesis of the 2-chloroethyl intermediates 10a-d which were then reacted with the appropriate phenylpiperazines. All compounds were tested for their antagonistic activity on 5-HT 2A receptors using inhibition of 5-hydroxytryptophan(5-HTP)-induced head twitches in mice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 17 publications
1
20
0
1
Order By: Relevance
“…10 In another study, multiple pharmacophoric features for 5-HT 2A antagonist action were identified including the two aromatic (hydrophobic) moieties. 11 …”
Section: Introductionmentioning
confidence: 99%
“…10 In another study, multiple pharmacophoric features for 5-HT 2A antagonist action were identified including the two aromatic (hydrophobic) moieties. 11 …”
Section: Introductionmentioning
confidence: 99%
“…In view of the growing biological importance of fused thiazoles, particularly thiazolo[3,2-a]pyrimidines, 32,33 it was of interest to synthesize 5-oxo-3-phenyl-N-(4-phenylthiazol-2-yl)-5H-thiazolo[3,2-a]pyrimidine-6-carboxamide. This bicyclic system is considered as a thia-analogue of the natural purine bases, adenine and guanine.…”
Section: Resultsmentioning
confidence: 99%
“…The 5-HT 2A receptor has been implicated as a therapeutic target for schizophrenia and depression. 4 5-HT 2 receptors were first identified in 1979 and since the early 1980s, numerous, structurally diverse antagonists of this receptor have been published ( Fig. 1).…”
Section: Introductionmentioning
confidence: 99%